Impact of Subclinical Mastitis on Reproductive Performance of Dairy Animals - Ghani, Muhammad Waseem; Bin, Liu; Birmani, Muhammad Waseem; Nawab, Aamir; Cun, Lang Guan; Ye, Li; Mei, Xiao (International Journal of Veterinary Sciences Research, 2019)
According to the international dairy federation, the dairy sector provides up to one billion livelihoods around the globe. Albeit, it faces many challenges including the two potentially threatening diseases which are mastitis and infertility. Both are complex multifactorial diseases, and mastitis is associated with causing infertility. Mastitis is an intramammary infection (IMI) and it occurs in two forms, clinical and subclinical. Mastitis being the infection of mammary glands, directly affects milk production to reduce its quality and quantity and indirectly hinders the reproductive performance of dairy animals. It negatively affects the reproduction parameters of dairy animals including, an increase in days open, a decrease in pregnancy rates, and increases chances of early embryonic losses and abortion. The chronic cases of mastitis lead toward the infertility of dairy animals and both of these diseases are responsible for increasing the culling rate and decreasing the profitability of a dairy farm. The objective of this study is to illustrate the influence of subclinical mastitis on reproduction parameters of dairy animals including, days open, days to the first service after calving, pregnancy rates, abortion, and embryonic losses. The relation between mastitis and infertility will be explained mechanistically.